1996
DOI: 10.1042/bj3190293
|View full text |Cite
|
Sign up to set email alerts
|

The CDC2-related kinase PITALRE is the catalytic subunit of active multimeric protein complexes

Abstract: PITALRE is a human protein kinase identified by means of its partial sequence identity to the cell division cycle regulatory kinase CDC2. Immunopurified PITALRE protein complexes exhibit an in vitro kinase activity that phosphorylates the retinoblastoma protein, suggesting that PITALRE catalyses this phosphorylation reaction. However, the presence of other kinases in the immunopurified complex could not be ruled out. In the present work, an inactive mutant of the PITALRE kinase has been used to demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 13 publications
2
74
0
Order By: Relevance
“…In general terms, activation of a cyclin/CDK pair occurs by upregulation of the rate limiting subunit, most often the cyclin regulatory subunit, by post-translational modi®cations a ecting either subunit and/or by abrogation of the interaction of CDK-inhibitors (CKIs) with either the CDK or the cyclin/CDK pair (GranÄ a and Reddy, 1995; Morgan, 1997;Xiong, 1996). Since our initial experiments in 293 cells overexpressing CDK9 suggested that p95 (cyclin T1) could be limiting for activation of CDK9 (Garriga et al, 1996a), we sought to determine if the levels of cyclin T1 are regulated during T cell activation. Thus, PBLs were obtained as described in Materials and methods section and incubated with PMA, PHA or TNF-a for 72 h. Activation of PBLs with either PHA or PMA, which are known to stimulate T cells through independent pathways, resulted in a sharp upregulation of cyclin T1, together with a more modest increase in the level of the CDK9 subunit (Figures 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general terms, activation of a cyclin/CDK pair occurs by upregulation of the rate limiting subunit, most often the cyclin regulatory subunit, by post-translational modi®cations a ecting either subunit and/or by abrogation of the interaction of CDK-inhibitors (CKIs) with either the CDK or the cyclin/CDK pair (GranÄ a and Reddy, 1995; Morgan, 1997;Xiong, 1996). Since our initial experiments in 293 cells overexpressing CDK9 suggested that p95 (cyclin T1) could be limiting for activation of CDK9 (Garriga et al, 1996a), we sought to determine if the levels of cyclin T1 are regulated during T cell activation. Thus, PBLs were obtained as described in Materials and methods section and incubated with PMA, PHA or TNF-a for 72 h. Activation of PBLs with either PHA or PMA, which are known to stimulate T cells through independent pathways, resulted in a sharp upregulation of cyclin T1, together with a more modest increase in the level of the CDK9 subunit (Figures 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies found most of the active PITALRE in high molecular weight complexes containing a number of unidenti®ed proteins. We had suggested that one of these proteins, p95, might be a positive regulatory subunit because the kinase activity of ectopically overexpressed PITALRE seemed to be limited by the amount of p95 (Garriga et al, 1996a). Subsequently, the large subunits of both Drosophila (Peng et al, 1998b) and human (Peng et al, 1998a;Wei et al, 1998) P-TEFb were cloned and found to be cyclin proteins.…”
Section: Introductionmentioning
confidence: 99%
“…pRC/CMV-CDK9 and pRC/CMV-CDK9n have been described (Garriga et al, 1996). The pRc/CMV-Cyclin T was constructed by inserting the EcoRI ± NcoI fragment from GST-CyclinT containing the full-length CyclinT1 cDNA into the EcoRV site of pCDNA3 (Invitrogen) via blunt ligation.…”
Section: Plasmidsmentioning
confidence: 99%
“…GAL4-CDK9 was constructed by inserting the NcoI ± EcoRI fragment from GST-CDK9 bearing the full-length cDNA into the SmaI site of pSG424 via blunt ligation. In a similar way GAL4-CDK9dn was constructed with the NcoI ± EcoRI fragment derived from pRC/CMV-CDK9dn (Garriga et al, 1996). The GAL4-CDK5 was obtained by inserting the SmaI fragment from GST-CDK5 containing the full length CDK5 cDNA into the EcoRI site of pSG424 via blunt ligation.…”
Section: Plasmidsmentioning
confidence: 99%
“…Cells were refed 4 h before transfection. Transfections were carried out following standard calcium-phosphate DNA precipitation procedure (Ausubel et al, 1988;Garriga et al, 1996). Plasmid DNA amounts were normalized with the corresponding empty plasmids.…”
Section: Antibodiesmentioning
confidence: 99%